2017
DOI: 10.3847/2041-8213/aa5d9f
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Rapid Orbital Decay of WASP-18b

Abstract: The WASP-18 system, with its massive and extremely close-in planet, WASP-18b (M p =10.3M J , a=0.02 au, P=22.6 hr), is one of the best-known exoplanet laboratories to directly measure Q′, the modified tidal quality factor and proxy for efficiency of tidal dissipation, of the host star. Previous analysis predicted a rapid orbital decay of the planet toward its host star that should be measurable on the timescale of a few years, if the star is as dissipative as is inferred from the circularization of close… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 48 publications
7
67
2
Order By: Relevance
“…Here and elsewhere, this limit was obtained by calculating the 95%-confidence limit on dP/dt and then applying Equation (1) to convert it into a limit on Q . The uncertainty of 0.4 is based on the propagation of the uncertainties in M p /M and a/R from Table 1. Our result for WASP-18 is consistent with the 2-σ limit Q > 10 6 derived by Wilkins et al (2017).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here and elsewhere, this limit was obtained by calculating the 95%-confidence limit on dP/dt and then applying Equation (1) to convert it into a limit on Q . The uncertainty of 0.4 is based on the propagation of the uncertainties in M p /M and a/R from Table 1. Our result for WASP-18 is consistent with the 2-σ limit Q > 10 6 derived by Wilkins et al (2017).…”
Section: Introductionsupporting
confidence: 91%
“…planet's mass is large enough that the system is not formally unstable to tidal decay, although the period may be shrinking as the system approaches synchronization. Wilkins et al (2017) (Ricker et al 2015), adding high-precision transit times to the existing ephemeris.…”
Section: Introductionmentioning
confidence: 99%
“…For hot Jupiters that have been monitored over baselines exceeding 10 years, secular changes in their orbital periods are currently being constrained to a precision of 10 msec yr −1 (Wilkins et al 2017;Maciejewski et al 2018;Baluev et al 2019;Petrucci et al 2020;Patra et al 2020). This is roughly commensurate with the level of signal many outer companions are expected to induce ( Figure 5).…”
Section: 3mentioning
confidence: 99%
“…Many groups have searched for direct evidence of tidal decay in individual systems as a secularly decreasing period. However, no studies have found unambiguous evidence of tidal inspiral (e.g., Maciejewski et al 2016; Corresponding author: Jacob H. Hamer jhamer3@jhu.edu kschlaufman@jhu.edu Patra et al 2017;Wilkins et al 2017;Maciejewski et al 2018;Bouma et al 2019). In most hot Jupiter systems, no departure from a linear ephemeris has been observed (e.g., HAT-P-23, KELT-1, .…”
Section: Introductionmentioning
confidence: 99%